State and state of charge estimation for a latent heat storage - Barz, Tilman; Sommer, Andreas; Walter, Sebastian F.; Bock, Hans Georg; Körkel, Stefan (Control engineering practice, 2018)
A nonlinear state observer is designed for a thermal energy storage with solid/liquid phase change material (PCM). Using a physical 2D dynamic model, the observer reconstructs transient spatial temperature fields inside the storage and estimates the stored energy and the state of charge. The observer has been successfully tested with a lab-scale latent heat storage with a single pass tube bundle and the phase change material located in a shell around each tube. It turns out that the observer robustly tracks the real process data with as few as four internal PCM temperature sensors.